Corticotrophin releasing factor increases ascending colon volume after a fructose test meal in healthy humans: a randomised control trial - Murray, Kathryn; Lam, Ching; Rehman, Sumra; Marciani, Luca; Costigan, Carolyn; Hoad, Caroline; Lingaya, Melanie; Banwait, Rawinder; Bawden, Stephen; Gowland, Penny A.; Spiller, Robin C. (American Society for Nutrition, 2016)
Background: Poorly absorbed, fermentable carbohydrates can provoke irritable bowel syndrome (IBS) symptoms by escaping absorption in the small bowel and being rapidly fermented in the colon in some susceptible subjects. IBS patients are often anxious and stressed and stress accelerates small bowel transit which may exacerbate malabsorption.